Verbal and Nonverbal Memory in Primary Progressive Aphasia: The Three Words-Three Shapes Test - Weintraub, Sandra (IOS Press, 2013)
Objectives: To investigate cognitive components and mechanisms of learning and memory in primary progressive aphasia (PPA) using a simple clinical measure, the Three Words Three Shapes Test (3W3S). Background: PPA patients can complain of memory loss and may perform poorly in standard tests of memory. The extent to which these signs and symptoms reflect dysfunction of the left hemisphere language versus limbic memory network remains unknown. Methods: 3W3S data from 26 patients with a clinical diagnosis of PPA were compared with previously published data from patients with typical dementia of the Alzheimer type (DAT) and cognitively healthy elders. Results: PPA patients showed two bottlenecks in new learning. First, they were impaired in the effortless (but not effortful) on-line encoding of verbal (but not non-verbal) items. Second, they were impaired in the retrieval (but not retention) of verbal (but not non-verbal) items. In contrast, DAT patients had impairments also in effortful on-line encoding and retention of verbal and nonverbal items. Conclusions: PPA selectively interferes with spontaneous on-line encoding and subsequent retrieval of verbal information. This combination may underlie poor memory test performance and is likely to reflect the dysfunction of the left hemisphere language rather than medial temporal memory network.